The driving force: Motivation in special Olympians - Farrell, R. J.; Crocker, P. R. E.; McDonough, M. H.; Sedgwick, A. W. (Adapted Physical Activity Quarterly, 2004)
Special Olympics programs provide competitive sport opportunities for athletes with intellectual disabilities. This study investigated athletes' perceptions of motivation in Special Olympics. Using Self-Determination Theory (SDT) as a guiding framework to explore athletes' experiences, 38 Special Olympians (21 males and 17 females) from British Columbia, Canada were interviewed. The data suggested that factors that enhanced autonomy, competence, and relatedness were linked to the participants' motivation in Special Olympics programs. These factors included positive feedback, choice, learning skills, demonstrating ability, friendships, social approval, and fun. Social support from significant others was a key factor related to participation motivation. There was also evidence for the motivating aspects of extrinsic rewards. Motivation was undermined primarily by conflicts with coaches and teammates.